Incorporation of industrial sludge in bricks production / Shah Buddin M.M.H ... [et al.] - Shah Buddin, M.M.H; Kharuddin, K; Fadilah, A.H.H; Mohammad Ramli, M.F; Hamil, M.S; Arsad, A (2018)
Incorporation of industrial sludge as an additional component in clay bricks was investigated in this study. This study aims to assess the effectiveness of utilizing industrial sludge into clay bricks and to evaluate the optimum amount of industrial sludge (by mass ratio) to be added into clay bricks. Clay bricks were produced at different mass ratios of industrial sludge to clay (without considering water mass): 0%, I 0%, 20%, 30%. & 40%, know11 as control, mixture type A, type B, type C, and type D, respectively. The mass of water added to each mixture is 40% of its clay mass. It has been found out that, mixture type A is the strongest clay brick mixture, which able to withstand 18.17 N/mm2 of compression strength. That finding was supported by the fact that the amount of industrial sludge in the brick is inversely proportional to the compression strength of the brick. The porosity of .the clay bricks does affect the water absorption. It has ,water absorption of 37.87%, and also passed the efflorescence test with no noticeable deposit of efflorescence on its surface. Furthermore, counter-productive data were recorded as the mass ratio of industrial sludge to clay ( without considering water mass) increases.